(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
Vocational education must be flexible to address industrial challenges and prepare students for workforce participation. However, there is still a lack of innovative digital learning media that integrates STEM approaches to foster creativity in vocational contexts. This study aimed to design interactive digital book learning media based on STEM approaches, ensure its suitability for vocational high school students, and evaluate its usability at the SMK level. The research employed the ADDIE model, implemented holistically from analysis through evaluation. Validation results indicated a feasibility score of 94.67% for the media component and 95.56% for the material component, both categorized as Very Valid. Usability testing with students yielded a feasibility score of 99.01%, classified as Very Feasible. Furthermore, comparative analysis of pre- and post-treatment scores revealed an average improvement of 36.16, with a normalized gain of 86.71, interpreted as High. These findings demonstrate that the use of STEM-based interactive digital books effectively enhances creative thinking skills among vocational high school students, particularly those in the DPIB program. The implications of this study highlight the potential of STEM-integrated digital media as a sustainable learning innovation that can be adopted across vocational education settings to strengthen students’ creativity and readiness for future industry demands.